Literature Review : Analisis Hubungan Jenis Persalinan Dengan Waktu Pengeluaran Kolustrum Pada Ibu Bersalin Kala IV di Rumah Sakit dan Praktek Mandiri Bidan Diwilayah Kota Palembang - Merisa Riski; Ahmad Arif; Sunarti Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The type of mother's delivery is one of the factors that influence lolustrum expenditure. Normal delivery and caesarean section (SC) result in psychological changes in the mother of pain, and are related to the administration of drugs to the mother which can affect colostrum excretion immediately after delivery. Percentage of SC deliveries in Hospitals and Midwives' Independent Practices in Palembang City Region. As many as 17.5%, this figure is the highest proportion of cesarean section in South Sumatra Province. While the coverage of exclusive breastfeeding in Hospitals and Independent Midwives Practices in the Palembang City Region, itself is the lowest in South Sumatra Province, which is 24.5%. The purpose of this study was to determine the relationship between the type of delivery and the time of expulsion of colostrum in mothers in the fourth stage of labor at the Hospital and Independent Practice of Midwives in the City of Palembang in 2023. This type of research was analytic observational with a prospective cohort design. The research sample consisted of 35 respondents in the group without risk factors and 35 respondents with risk factors. This research began in November 2022 until April 2023. Data collection was carried out by means of interviews and observations. Data analysis using Chi-Square. Characteristics of mothers in this study were age, parity, nutritional status, and mother's education. The results of bivariate analysis showed that the type of CS delivery slowed colostrum excretion up to > 120 minutes by 1.75 (p=0.031; 95% CI; 1.028-2.981). The conclusion of this type of SC delivery can slow colostrum expulsion time by > 120 minutes.